Tradycyjne formy kultu św. Mikołaja w tomaszowskich dekanatach diecezji zamojsko-lubaczowskiej - Nowak, Józef (Vox Patrum, 2002)
The cult of saints is a significant aspect of the Paschal mystery. The cult practices concerning the saints mainly include the prayer and offerings. They are of religious and social dimensions. Integration of the rural parish community takes place through the common prayer at home, participation in liturgical services and performance of the deeds of love. Besides, customs, rites and folk beliefs point to the scope of the saints’ cult. They are reflected in songs, prayers, proverbs, tales and legends.